Household-level impacts of the March 2025 earthquake in Myanmar: Findings from the ninth round of the Myanmar Household Welfare Survey (July-October 2025) - van Asselt, Joanna; Ei Win, Hnin; Aung, Zin Wai (International Food Policy Research Institute, 2026)
This report presents key findings on the impacts of the earthquake that hit Myanmar on March 28, 2025, along with insights into the ongoing recovery, based on the ninth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey. This survey was conducted between July and October 2025, with a recall period covering April to October.